Schiff Base Compounds as Fluorescent Probes for the Highly Sensitive and Selective Detection of Al3+ Ions - Yanling Pang; Desu Meng; Jian Liu; Shengxia Duan; Jingru Fan; Longyu Gao; Xinshu Long (Molecules, 2023)
Two new Schiff base fluorescent probes (L and S) were designed for selectively detecting Al3+ ions in aqueous medium. Structural characterization of the purely synthesized compounds was acquired by IR, 1H NMR and 13C NMR. Moreover, their photochromic and fluorescent behaviors have been investigated systematically by UV–Vis absorption and fluorescence spectra. The two probes have both high selectivity and sensitivity toward Al3+ ions in aqueous medium. The 2:1 stoichiometry between the Al3+ and probes was verified by Job’s plot. Moreover, the limits of detection (LOD) for Al3+ by L and S were 1.98 × 10−8 and 4.79 × 10−8 mol/L, respectively, which was much lower than most previously reported probes. The possible recognition mechanism was that the metal ions would complex with Schiff base probes because of the prevalence of the species optimal for complex formation, inhibiting the structural isomerization of conjugated double bonds (-C=N-), inhibiting the proton transfer process in the excited state of the molecules and resulting in changes of its color and fluorescence behavior. Furthermore, the probes will have potential applications for selectively, detecting Al3+ ions in the environmental system with high accuracy and providing a new strategy for the design and synthesis of multi-functional sensors.